Comparative assessment of the SjSAP4-incorporated gold immunochromatographic assay for the diagnosis of human schistosomiasis japonica - Yi Mu; Jonas Rivera; Jonas Rivera; Donald P. McManus; Kosala G. Weerakoon; Allen G. Ross; Remigio M. Olveda; Catherine A. Gordon; Catherine A. Gordon; Hong You; Hong You; Malcolm K. Jones; et al. (Frontiers Media S.A., 2023)
BackgroundSchistosomiasis, a disease caused by parasites of the genus Schistosoma, remains a global public health threat. This study aimed to validate the diagnostic performance of a recently developed gold immunochromatographic assay (GICA) for the detection of S. japonicum infection in a rural endemic area of the Philippines.MethodsHuman clinical samples were collected from 412 subjects living in Laoang and Palapag municipalities, Northern Samar, the Philippines. The presence of Schistosoma-specific antibodies in serum samples was tested with the SjSAP4-incorporated GICA strips and the results were converted to fully quantitative data by introducing an R value. The performance of the established GICA was further compared with other diagnostic tools, including the Kato-Katz (KK) technique, point-of-care circulating cathodic antigen (POC-CCA), droplet digital (dd) PCR, and enzyme-linked immunosorbent assays (ELISAs).ResultsThe developed GICA strip was able to detect KK positive individuals with a sensitivity of 83.3% and absolute specificity. When calibrated with the highly sensitive faecal ddPCR assay, the immunochromatographic assay displayed an accuracy of 60.7%. Globally, the GICA assay showed a high concordance with the SjSAP4-ELISA assay. The schistosomiasis positivity rate determined by the GICA test was similar to those obtained with the SjSAP4-ELISA assay and the ddPCR assay performed on serum samples (SR_ddPCR), and was 2.3 times higher than obtained with the KK method.ConclusionThe study further confirms that the developed GICA is a valuable diagnostic tool for detecting light S. japonicum infections and implies that this point-of-care assay is a viable solution for surveying endemic areas of low-intensity schistosomiasis and identifying high-priority endemic areas for targeted interventions.